Studies on the Effect of Spacing on the Wood Quality in some Clones of Populus deltoides - Chauhan, Laxmi; Gupta, Sangeeta; Madhwal, R. C.; Pandey, Rajiv (Indian Forester, 2001)
The results of a study on the effect of spacing on wood specific gravity, selected wood anatomical parameters and tree growth in two 9-10 year old plantations of 3 clones of Populus deltoides are reported. Significant effect of spacing was observed on specific gravity, fibre length, fibre diameter, vessel diameter, tree height and girth. While specific gravity shows an increase at wide spacing, fibre length has been found to decrease in the two plantations.